2012
DOI: 10.1007/s11427-012-4419-3
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of the rare medicinal plant Dendrobium officinale based on naringenin, bibenzyl, and polysaccharides

Abstract: The aim of this study was to establish a method for discriminating Dendrobium officinale from four of its close relatives Dendrobium chrysanthum, Dendrobium crystallinum, Dendrobium aphyllum and Dendrobium devonianum based on chemical composition analysis. We analyzed 62 samples of 24 Dendrobium species. High performance liquid chromatography analysis confirmed that the four low molecular weight compounds 4′,5,7-trihydroxyflavanone (naringenin), 3,4-dihydroxy-4′,5-dimethoxybibenzyl (DDB-2), 3′,4-dihydroxy-3,5′… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 20 publications
2
37
0
Order By: Relevance
“…The typical chromatograms and calculated contents of the released monosaccharides after acid hydrolysis in water extracts of all Dendrobium samples were summarized in Fig. 3 and Table 1, respectively, and further confirmed the obtained results in previous reports [24]. The analysis demonstrated that sugar composition exhibited highly qualitative consistence in all Dendrobium samples.…”
Section: Sugar Composition Analysissupporting
confidence: 88%
See 2 more Smart Citations
“…The typical chromatograms and calculated contents of the released monosaccharides after acid hydrolysis in water extracts of all Dendrobium samples were summarized in Fig. 3 and Table 1, respectively, and further confirmed the obtained results in previous reports [24]. The analysis demonstrated that sugar composition exhibited highly qualitative consistence in all Dendrobium samples.…”
Section: Sugar Composition Analysissupporting
confidence: 88%
“…This herb has a unique chemical profile, in which saccharides account for up to 70 %, along with some small molecules, such as bibenzyls and phenanthrenes [21][22][23], etc. Quality evaluation focusing on small molecules [24,25] has failed to efficiently distinguish D. officinale from other Dendrobium sp. And in these studies, the investigated constituents were less than 0.21 % of the whole herb material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monosaccharide profile has been successfully applied for QC of Dendrobii Officinalis Caulis, which is a rare medicinal plant (113). Chinese Pharmacopoeia (2010 Edition) documented that the ratio of mannose and glucose in Dendrobii Officinalis Caulis should be 2.4-8.0 (114).…”
Section: Quantification Analysismentioning
confidence: 99%
“…It is an epiphytic and perennial herb, and is mainly distributed in the south areas of China. Dendrobium officinale has many kinds of main active ingredient in which polysaccharide is the main ingredient (Chen et al, 2012). Previous studies demonstrate that Dendrobium officinale polysaccharide (DDP) possesses antioxidant, immunomodulatory and anti-hypoglycaemic activities (Pan et al, 2014;Cai et al, 2015).…”
Section: Introductionmentioning
confidence: 99%